An Ethernet Based Monitoring and Controlling Of Home Appliances Using Rabbit Processor (International Journal of Engineering and Computer Science, 2014)
The aim of home automation is to control home devices from a central control point. In this paper, we present the design and implementation of a low cost but yet flexible and secure internet based home automation system. The communication between the devices is wireless. The protocol between the units in the design is enhanced to be suitable for most of the appliances. The system is designed to be low cost and flexible with the increasing variety of devices to be controlled. Networking is a major component of the processes and control instrumentation systems as the network’s architecture solves many of the Industrial automation problems. There is a great deal of benefits in the process of industrial parameters to adopt the Ethernet control system. Hence an attempt has been made to develop an Ethernet based remote monitoring and control of home appliances. In the present work the experimental result shows that remote monitoring and control system (RMACS) over the Ethernet.